Microstructure of Bentonite in Iron Ore Green Pellets. (7th January 2014) - Bhuiyan, Iftekhar U.; Mouzon, Johanne; Schröppel, Birgit; Kaech, Andres; Dobryden, Illia; Forsmo, Seija P.E.; Hedlund, Jonas
Abstract: Sodium-activated calcium bentonite is used as a binder in iron ore pellets and is known to increase strength of both wet and dry iron ore green pellets. In this article, the microstructure of bentonite in magnetite pellets is revealed for the first time using scanning electron microscopy. The microstructure of bentonite in wet and dry iron ore pellets, as well as in distilled water, was imaged by various imaging techniques (e.g., imaging at low voltage with monochromatic and decelerated beam or low loss backscattered electrons) and cryogenic methods (i.e., high pressure freezing and plunge freezing in liquid ethane). In wet iron ore green pellets, clay tactoids (stacks of parallel primary clay platelets) were very well dispersed and formed a voluminous network occupying the space available between mineral particles. When the pellet was dried, bentonite was drawn to the contact points between the particles and formed solid bridges, which impart strength to the solid compact.